ANALYSIS OF THE EFFECT OF HDI, GRDP, AND MINIMUM WAGES ON POVERTY IN CENTRAL JAVA FOR THE PERIOD OF 2011-2020 - I Kadek Mahatma Avigna; Ari Musa Apriadi; Princess Princess (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2022)
This study aims to analyze the effect of the Gross Regional Domestic Product, Minimum Wage and Human Development Index partially or simultaneously on the poverty level in the Regency/City of Central Java Province (2011-2020). This study uses secondary data covering 35 districts or cities in Central Java Province based on cross section data and from 2011 to 2020 on time series data. The analytical method used is panel data regression analysis with Random Effect Model (REM) or Generalized Least Square (GLS). The results showed that simultaneously GRDP, UMK, HDI and Population had an effect on the level of poverty in Central Java Province. While partially (1) GRDP has a significant negative effect on the level of poverty in Central Java Province; (2) MSE has no effect on the poverty level in Central Java Province; (3) HDI has a significant negative effect on the poverty level in Central Java Province.